Studi Fenomenologi terhadap Pasien Hipertensi - Ruth Jelina Br Sitepu; Lyna M. N. Hutapea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine phenomenological studies of hypertensive patients. This research method is qualitative research with a descriptive phenomenological approach that uses the Colaizzi model. Research results: Identified in 4 themes, namely: 1. Knowledge, 2. Activities, 3. Stress/Emotional Levels, 4. Family History. In conclusion, Through the experience of clients who suffer from hypertension, information about knowledge, activities, stress/emotional levels, and family history are essential in influencing their health condition both before experiencing hypertension and after suffering from hypertension. Keywords: Hypertension, Experience, Qualitative